Fish oil attenuated dystrophic muscle markers of inflammation via FFA1 and FFA4 in the mdx mouse model of DMD. Issue 6 (13th November 2020) - Maciel Junior, Marcos; Camaçari de Carvalho, Samara; Saenz Suarez, Paula Andrea; Santo Neto, Humberto; Marques, Maria Julia
Abstract: In the present study we investigated the involvement of free fatty acid (FFA) receptors in the anti‐inflammatory role of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in dystrophic muscles, by administering FFA blockers in the mdx mouse model of dystrophy. Mdx mice (3 months‐old) were treated with fish oil capsules (FDC Vitamins; 0.4 g EPA and 0.2 g DHA; gavage) alone or concomitant to FFA1 and FFA4 blockers (GW1100 and AH7614; i.p.). C57BL/10 mice (3 months‐old) and untreated‐ mdx mice received mineral oil and were used as controls. After 1 month of treatment, plasma markers of myonecrosis (total and cardiac creatine kinase; CK), the levels of FFA1 and FFA4 and of the markers of inflammation, nuclear transcription factor kappa B (NFkB), tumor necrosis factor alpha (TNF‐α) and interleukin 1β (IL‐1β) were analyzed in the diaphragm muscle and heart by western blot. Fish oil significantly reduced total CK, cardiac CK and the levels of NFkB (diaphragm), and of TNF‐α and IL‐1β (diaphragm and heart) in mdx . In the dystrophic diaphragm, FFA1 was increased compared to normal. Blockers of FFA1 and FFA4 significantly inhibited the effects of fish oil treatment in both dystrophic muscles. The anti‐inflammatory effects of fish oil in dystrophic diaphragm muscle and heart were mediated through FFA1 and FFA4. Resumo: No presente estudo investigamos o envolvimento de receptores de ácidos graxos livres (FFA) no efeito anti‐inflamatório dos ácidos eicosapentaenoico (EPA) e docosahexaenoico (DHA) em músculos distróficos, administrando bloqueadores de FFA no camundongo mdx, modelo de distrofia. Camundongos mdx (3 meses de idade) foram tratados com cápsulas de óleo de peixe (FDC Vitamins; 0.4 g EPA e 0.2 g DHA; gavagem) ou com cápsulas de óleo de peixe concomitante a bloqueadores de FFA1 e FFA4 (GW1100 e AH7614; i.p.). Camundongos C57BL/10 (3 meses de idade) e camundongos mdx não tratados receberam óleo mineral e serviram de controle. Após 1 mês de tratamento, marcadores plasmáticos de mionecrose (creatina quinase total e cardíaca; CK), os níveis de FFA1 e FFA4 e dos marcadores de inflamação fator de transcrição nuclear kappa B (NFkB, nuclear transcription factor kappa B), fator de necrose tumoral alpha (TNF‐α, tumor necrosis factor alpha) e interleucina 1β (IL‐1β) foram analisados no músculo diafragma e no coração através de western blot. O óleo de peixe reduziu de forma significativa a CK total, CK cardíaca e os níveis de NFkB (diafragma), TNF‐α e IL‐1β (diafragma e coração) no mdx . No diafragma distrófico, FFA1 estava aumentado comparado ao normal. Os bloqueadores de FFA1 e FFA4 inibiram de forma significativa os efeitos do tratamento com óleo de peixe em ambos músculos distróficos. Os efeitos anti‐inflamatórios do óleo de peixe nos músculos distróficos diafragma e cardíaco foram mediados por FFA1 e FFA4.